Gentisaldehyde and Its Derivative 2,3-Dihydroxybenzaldehyde Show Antimicrobial Activities Against Bovine Mastitis Staphylococcus aureus - Schabauer, Andrea; Zutz, Christoph; Lung, Barbara; Wagner, Martin; Rychli, Kathrin (Frontiers in Veterinary Science, 2018)
Bovine mastitis is a worldwide disease of dairy cattle associated with significant economic losses for the dairy industry. One of the most common pathogens responsible for mastitis is Staphylococcus (S.) aureus. Due to the development and spreading of antibiotic resistance, the search for novel antimicrobial substances against S. aureus is of great importance. The aim of this study was to evaluate the two dihydroxybenzaldehydes for the prevention of bovine mastitis. Therefore we determined the minimal inhibitory concentration (MICs) of gentisaldehyde (2,5-dihydroxybenzaldehyde) and 2,3-dihydroxybenzaldehyde of a diverse set of 172 bovine mastitis S. aureus isolates using an automates robot-based microdilution method. To characterize the bovine isolates we determined the genotype by spa-typing, the antimicrobial resistance to eight antibiotic classes using the disk diffusion method and the MICs of three commonly used antiseptics (benzalkonium chloride, chlorhexidine and iodine). Further we investigated the cytotoxicity of gentisaldehyde and 2,3-dihydroxybenzaldehyde in bovine mammary epithelial MAC-T cells using the XTT assay. The S. aureus strains showed a high genetic diversity with 52 different spa-types, including five novel types. Antibiotic susceptibility testing revealed that 24% of isolates were resistant to one antimicrobial agent and 3% of isolates were multi-resistant. The occurrence of antibiotic resistance strongly correlated with the spa-type. Both dihydroxybenzaldehydes showed antimicrobial activities with a MIC50 of 500 mg/L. The MIC of gentisaldehyde significantly correlated with that of 2,3-dihydroxybenzaldehyde, whereas no correlation was observed with the MIC of the three antiseptics. Cytotoxicity testing using bovine mammary epithelial MAC-T cells revealed that gentisaldehyde and 2,3-dihydroxybenzaldehyde show low toxicity at MIC50 and MIC90 concentrations. In conclusion, gentisaldehyde and 2,3-dihydroxybenzaldehyde exhibited antimicrobial activities against a diverse range of bovine mastitis S. aureus strains at low-cytotoxic concentrations. Therefore, both compounds are potential candidates as antiseptics to prevent bovine mastitis and to reduce the use of antibiotics in dairy cows.